SOCIAL INTERACTIONS STUDENTS DISABLED BODY IN LEARNING PROCESS - Krismiyanto, Alfonsus; Ngw, MS, Prof. Dr. Bonaventura; Sholahuddin, MS, Prof. Dr. H Agus (IJRDO - Journal of Social Science and Humanities Research, 2018)
Based on the facts about the importance of community and society to human life, on the one hand has the right to be assisted by society, but on the one hand it has the right to give its support to society. The research problem formulated as : (1) What factors are behind the social interaction of disabled students with teachers in the learning process at Bhakti Luhur School Malang City? (2) How does a disabled student develop social interaction with the teacher in learning process at Bhakti Luhur School Malang City? There are also objectives are (1) Analyzing the factors behind the social interaction of disabled students with teachers in the learning process at Bhakti Luhur School Malang City; (2) Analyzing social interaction developed by disabled students with teachers in learning process at Bhakti Luhur school Malang city. The method used is qualitative research method. Based on the results of research and discussion, this research can be concluded that there are (1) Factors that Dissolve Social Interaction of Student Disabilities in Learning; and (2) Development of Social Interaction on Students with Disabilities in Learning. The results of this study reinforce the theory of social interaction David A. Karp dan William C. Yoels